2012
DOI: 10.1523/jneurosci.0698-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Pharmacology of Native P2X Receptors in Rat and Primate Sensory Neurons

Abstract: Evidence suggesting the involvement of P2X2 and P2X3 in chronic pain has been obtained mostly from rodent models. Here we show that rodents may be poor predictors of P2X3 pharmacology in human. We demonstrate that monkey and human dorsal root ganglion (DRG) neurons do not express appreciable levels of P2X2 subunit, contrary to rat sensory neurons. Additionally, we report functional P2X3 activity in monkey DRG neurons and confirm the absence of functional P2X2/3 receptors. Interestingly, native P2X3 receptors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 27 publications
0
51
0
1
Order By: Relevance
“…Indeed, hypoxia caused a fourfold increase in release of acetylcholine and ATP from human CB slices. This study is important strategically as it gives clear evidence that the rodent models studied to date have relevance to chemosensory transduction mechanisms in humans, something questioned recently (Serrano et al, 2012). This is supported by transcriptomic findings relating to hypoxia sensing, although differences were also identified (Mkrtchian et al, 2012).…”
Section: Human Carotid Body and Purinergic Mechanismsmentioning
confidence: 52%
See 2 more Smart Citations
“…Indeed, hypoxia caused a fourfold increase in release of acetylcholine and ATP from human CB slices. This study is important strategically as it gives clear evidence that the rodent models studied to date have relevance to chemosensory transduction mechanisms in humans, something questioned recently (Serrano et al, 2012). This is supported by transcriptomic findings relating to hypoxia sensing, although differences were also identified (Mkrtchian et al, 2012).…”
Section: Human Carotid Body and Purinergic Mechanismsmentioning
confidence: 52%
“…Human P2X3 receptors produce relatively large responses with less desensitization compared to rat (Sundukova et al, 2012). Finally, a cross-species cellular expression of P2X2 and P2X3 receptor mRNA in dorsal root ganglia neurons in rat, monkey, and human revealed that P2X3 but not P2X2 was expressed in the primates (Serrano et al, 2012) supporting the notion that P2X3 receptors have a more dominant sensory role than P2X2 in humans. Therefore, these receptors will be considered below.…”
Section: Human Carotid Body and Purinergic Mechanismsmentioning
confidence: 56%
See 1 more Smart Citation
“…Despite the endogenous expression of at least three different P2Y receptor subtypes [34,35] HEK 293 cells are frequently used to study properties of P2X receptors [34,36]. To assess the role of P2XRs in inducing changes of intracellular Ca 2+ concentrations, some investigators often choose cell lines (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…TNP-ATP, a nonspecific antagonist, impedes the upward motion of the DF with a large steric bulk of trinitrophenyl moieties, and therefore inhibits channel opening [33] . RO-51, a bioavailable P2X3 antagonist, displays a two hundred-fold lower potency on human P2X3 (hP2X3) compared to rat P2X3 (rP2X3), due to two amino acids located in the DF domain, A197 and T202 ( Figure 3) [53] . Thus, the upward motion of the DF domain is also essential for the channel gating of P2X receptors, and small molecules interrupting this motion effectively block P2X receptors.…”
Section: Dorsal Fin Domainmentioning
confidence: 99%